Myocardial Work by Speckle Tracking Echocardiography Accurately Assesses Left Ventricular Function of Coronary Artery Disease Patients - Zhu, Huolan; Guo, Ying; Wang, Xiang; Yang, Chenguang; Li, Yi; Meng, Xuyang; Pei, Zuowei; Zhang, Ruisheng; Zhong, You; Wang, Fang (Frontiers in Cardiovascular Medicine, 2021)
Objective Myocardial work (MW) is a novel non-invasive method using speckle tracking echocardiography (STE) for assessing the left ventricular(LV) function. It incorporates global longitudinal strain (GLS) and afterload condition. We aimed to investigate this method for assessing the LV function in patients with coronary artery disease(CAD) with or without heart failure(HF). Methods We enrolled totally 150 individuals—50 each in the CAD with normal left ventricular ejection fraction (LVEF), CAD with heart failure, and healthy control group. Patients were divided into the normal blood pressure and hypertension (HTN) subgroups. Myocardial work (MW) was obtained from the pressure-strain loop using STE. The relationships between MW indices and conventional echocardiographic parameters were evaluated; MW indices were compared between the groups. Results Univariable and multivariable analysis showed that MW indices were strongly correlated with the LVEF. The global work index (GWI) was increased in CAD with normal LVEF subgroup with hypertension compared with the control (1922.29±393.07 VS 1639.72±204.57 mmHg%, p<0.05); and decreased in CAD patients with HF (No-HTN: 940.85±380.61 VS 1639.72±204.57 mmHg%, p<0.05; HTN: 857.31±369.34 VS 1639.72±204.57 mmHg%, p<0.05). The global waste work (GWW) was increased in all CAD subgroups compared with the control. The global constructive work (GCW) had the same tendency as GWI in the CAD patients. The global myocardial work efficiency (GWE) was decreased in all CAD patients. Conclusion Myocardial work by STE provides an accurate quantified assessment of the left ventricular function in patients with CAD. It offers additional information on LV function regarding disease progression.